The Fatigue Life Prediction of Welded Joints in Orthotropic Steel Bridge Decks Considering Weld-Induced Residual Stress and Its Relaxation Under Vehicle Loads - Wen Zhong; Youliang Ding; Yongsheng Song; Sumei Liu; Mengyao Xu; Xin Wang (Buildings)
The welded joints in steel bridges have a complicated structure, and their fatigue life is mainly determined by the real stress under the coupling effect of vehicle load stress, as well as weld-induced residual stress and its relaxation. Traditional fatigue analysis methods are inadequate for effectively accounting for weld-induced residual stress and its relaxation, resulting in a significant discrepancy between the predicted fatigue life and the actual fatigue cracking time. A fatigue damage assessment model of welded joints was developed in this study, considering weld-induced residual stress and its relaxation under vehicle load stress. A multi-scale finite element model (FEM) for vehicle-induced coupled analysis was established to investigate the weld-induced initial residual stress and its relaxation effect associated with cyclic bend fatigue due to vehicles. The fatigue damage assessment, considering the welding residual stress and its relaxation, was performed based on the S–N curve model from metal fatigue theory and Miner’s linear damage theory. Based on this, the impact of variations in traffic load on fatigue life was forecasted. The results show that (1) the state of tension or compression in vehicle load stress notably impacts the residual stress relaxation effect observed in welded joints, of which the relaxation magnitude of the von Mises stress amounts to 81.2% of the average vehicle load stress value under tensile stress working conditions; (2) the predicted life of deck-to-rib welded joints is 28.26 years, based on traffic data from Jiangyin Bridge, which is closer to the monitored fatigue cracking life when compared with the Eurocode 3 and AASHTO LRFD standards; and (3) when vehicle weight and traffic volume increase by 30%, the fatigue life significantly drops to just 9.25 and 12.13 years, receptively.